STEREOTYPING AFRICAN AMERICANS’ RACIAL IDENTITY ON VALERIE MARTIN’S PROPERTY - Rasiah Rasiah (Universitas Gadjah Mada, 2016)
This study is intended to analyze the persistence of African American stereotype in the contemporary slavery-themed novel authored by Valerie Martin, Property (2003). Valerie Martin is a white author, who seems to have changed the slavery discourse, but the stereotyping of African Americans is still there and built in a new form of stereotyping. Postcolonial analysis showed that the stereotyping of African Americansas ‘other’ existed in direct stereotyping and indirect stereotyping. Direct stereotyping is that the author directly uses the pejorative language and symbols in forming the African American character, meanwhile indirect stereotyping is the author using the shift of discourse that seemed worthy in describing the African American character, but in the same time it affirms the stereotype of the African American identity as inferior still exists, even in the so-called Post-racial era in the United States. Keywords: Representation, Stereotyping, Identity, Race, African American